A hyaluronan-based nanosystem enables combined anti-inflammation of mTOR gene silencing and pharmacotherapy. (1st September 2018) - Hou, Chunyan; Bai, Hu; Wang, Zhaojie; Qiu, Yuanhao; Kong, Li-Li; Sun, Feifei; Wang, Dongdong; Yin, Hong; Zhang, Xiaoli; Mu, Haibo; Duan, Jinyou
Highlights: A ROS responsive dexamethasone-conjugated hyaluronan derivative (HA-DSH) was synthesized. A HA-DSH caped CaP nanosystem was fabricated which showed excellent properties. Combined anti-inflammatory effect was achieved by the co-delivery of dexamethasone and mTOR siRNA with the nanosystem. Abstract: Accompanied by overproduction of oxidants and reduction of pH, inflammation is closely related to many diseases such as cancer, atherosclerosis, and asthma. Besides chemotherapeutic agents, the potential regulative role of autophagy in inflammation is being actively investigated. RNA interference (RNAi)-based gene therapy is widely explored for clinical therapy but seriously restricted by lack of suitable carriers. In this study, we synthesized a hyaluronan-based ROS-sensitive polymer which was expected to release loaded chemical drugs in inflammatory environment and further developed a stable and nontoxic co-delivery nanosystem of siRNA targeting autophagy suppressive gene and chemotherapeutic agents. The in vitro transfection study of this nanosystem revealed improved intracellular accumulation of siRNA and excellent gene silencing efficacy comparable to that of conventional cationic liposome. Moreover, the mRNA expression of inflammatory cytokines was remarkably decreased by our nanosystem. Considering its biocompatibility, transfection efficacy, and anti-inflammatory capability, this co-delivery nanosystem proclaimed to be a promising combined therapeutic strategy for enhanced anti-inflammatory therapy.